Clinical Evaluation of Sinonasal Lesions in Patients With Immunoglobulin G4-Related Disease. (December 2015) - Takano, Kenichi; Abe, Ayumi; Yajima, Ryoto; Kakuki, Takuya; Jitsukawa, Sumito; Nomura, Kazuaki; Himi, Tetsuo
Objectives: Immunoglobulin G4-related disease (IgG4-RD) is a systemic disease entity characterized by elevated serum IgG4 and extensive IgG4-positive plasma cell infiltration of various organs. Patients with IgG4-RD show nasal manifestations with chronic rhinosinusitis. The objective of this study was to evaluate the clinical characteristics of sinonasal lesions in patients with IgG4-RD. Methods: We evaluated radiological findings of sinonasal lesions in 79 patients with IgG4-RD who were divided into 3 groups according to severity. We also compared serological findings, including serum IgG4 and IgE levels, and eosinophil counts. Results: Rhinosinusitis was found in 41 patients (51.9%). Although there were no significant differences in the serum IgG4 and IgE levels of the groups, there was a significant increase in eosinophil counts (445 ± 311.9/mm 3 ) in Group C. Furthermore, 14 of the 41 patients with rhinosinusitis (34.1%) showed improvement after prednisolone administration. Patients with IgG4-RD and serum eosinophilia tend to also have sinonasal lesions. Conclusions: Rhinosinusitis is common in patients with IgG4-RD, and its pathogenesis can be similar to eosinophilic chronic rhinosinusitis.